Outcome evaluation of research for development work conducted in Ghana and Sri Lanka under the Resource, Recovery and Reuse (RRR) subprogram of the CGIAR Research Program on Water, Land and Ecosystems (WLE). - Sally, H.; Merrey, Douglas J. (CGIAR Research Program on Water, Land and Ecosystems, 2019)
This is the main report of an external evaluation of the Resource Recovery and Reuse Flagship of the Water Land and Ecosystems (WLE) CGIAR Research Program. WLE commissioned the study. The Evaluators interviewed researchers and partners in two countries, Ghana and Sri Lanka, and in Ghana visited two sites. They also interviewed key international partners and analyzed a wide range of documents, reports and publications. The evaluation was focused on understanding how and in what ways the research and other activities carried out by IWMI and supported by WLE contributed to the outcomes. In essence, the purpose was to understand the specific impact pathways from research to outputs and outcomes.